2019
DOI: 10.1002/mus.26673
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of small sensory fiber function in myotonic dystrophy type 1

Abstract: Background Myotonic dystrophy type 1 (DM1) is a multisystem disorder affecting the peripheral nervous system. However, studies evaluating somatic small fiber sensory nerve function, which may contribute to pain in DM1, are lacking. Methods Using quantitative sensory testing of the hand and foot, we evaluated Aδ and C‐fiber function. Of 20 adult DM1 patients recruited, 16 were analyzed. Their results were compared with those of 32 age‐ and sex‐matched controls. Results No DM1 patient had diabetes mellitus or cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, our ex vivo electrophysiology and calcium imaging data suggest that peripheral sensitization is likely not responsible for the pain-like behavior. While rigorous quantitative sensory testing in myotonic patients has remained limited, our preclinical data aligns with multiple studies that have demonstrated limited peripheral sensory neuron abnormalities in myotonic dystrophy patients (Hermans et al ., 2011; Peric et al ., 2013; Nojszewska et al ., 2015; Boland-Freitas & Ng, 2019). Nevertheless, we cannot rule out peripheral involvement as an initial priming event for central sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…However, our ex vivo electrophysiology and calcium imaging data suggest that peripheral sensitization is likely not responsible for the pain-like behavior. While rigorous quantitative sensory testing in myotonic patients has remained limited, our preclinical data aligns with multiple studies that have demonstrated limited peripheral sensory neuron abnormalities in myotonic dystrophy patients (Hermans et al ., 2011; Peric et al ., 2013; Nojszewska et al ., 2015; Boland-Freitas & Ng, 2019). Nevertheless, we cannot rule out peripheral involvement as an initial priming event for central sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that DM1 may involve the peripheral nervous system ( 2 – 4 ). Recently Boland-Freitas and Ng found indications of a subclinical small fiber neuropathy measured by quantitative sensory testing in patients with DM1 ( 5 ). Chronic pain has been reported in about 60%, and has been associated with fatigue, reduced motor function and quality of life ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%